2008
DOI: 10.1164/rccm.200804-617oc
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in HIV-infected Persons

Abstract: Rationale: Bacterial pneumonia is a major cause of morbidity for HIVinfected persons and contributes to excess mortality in this population. Objectives: To evaluate the frequency and risk factors for occurrence of bacterial pneumonia in the present era of potent antiretroviral therapy. Methods: We evaluated data from a randomized trial of episodic antiretroviral therapy. The study, Strategies for Management of Antiretroviral Therapy, enrolled 5,472 participants at 318 sites in 33 countries. Study patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 27 publications
6
32
0
2
Order By: Relevance
“…Bacterial pneumonia is closely linked to cigarette smoking and studies in both the pre-ART and ART eras have demonstrated a greatly increased risk of bacterial pneumonia in HIV-infected smokers [6, 13-15]. Furthermore, evidence now exists that cigarette smoking has become the single most important clinical risk factor for bacterial pneumonia in the HIV-infected population [14, 15]. Smoking effects on lung host defense, including adverse effects on alveolar macrophage function and chemotactic properties, may be an important contributing mechanism [16-18].…”
Section: Cigarette Smoking and Health Implications For The Hiv-infectmentioning
confidence: 99%
“…Bacterial pneumonia is closely linked to cigarette smoking and studies in both the pre-ART and ART eras have demonstrated a greatly increased risk of bacterial pneumonia in HIV-infected smokers [6, 13-15]. Furthermore, evidence now exists that cigarette smoking has become the single most important clinical risk factor for bacterial pneumonia in the HIV-infected population [14, 15]. Smoking effects on lung host defense, including adverse effects on alveolar macrophage function and chemotactic properties, may be an important contributing mechanism [16-18].…”
Section: Cigarette Smoking and Health Implications For The Hiv-infectmentioning
confidence: 99%
“…Both HIV and smoking are risk factors for suppression of local lung defenses and pulmonary diseases including a variety of bacterial pneumonias, acute bronchitis, and tuberculosis (Burns et al, 1996; Conley et al, 1996; Gordin et al, 2008; Hajjeh et al, 1999; Marrie, 1999; Miguez-Burbano et al, 2005; Nuorti et al, 2000; Tumbarello et al, 1998). Evidence exists that the lungs of HIV-positive individuals are especially susceptible to the damaging effects of cigarette smoke with reduction in pulmonary diffusing capacity and increased susceptibility to early development of emphysema (Crothers et al, 2006; Diaz, King, Wewers, et al, 2000; Diaz, King, Pacht, et al, 2000; Diaz et al, 1999; Diaz et al, 2003; Petrache et al, 2008).…”
Section: Rates Of Tobacco Consumption and Clinical Implications Amongmentioning
confidence: 99%
“…Among HIV-infected patients, the prevalence of tobacco smoking is very high, generally reported around 50% in European HIV cohorts [5], [6], compared to 27% in the general population of comparable age and gender [7]. Recent studies have confirmed the effect of tobacco smoking on respiratory tract infections in HIV-infected patients [8], [9], [10], and promoted tobacco smoking withdrawal as a priority. However, the benefit of tobacco withdrawal on the risk of bacterial pneumonia has not been quantified in such populations, exposed to other important risk factors such as HIV-related immunodeficiency [11].…”
Section: Introductionmentioning
confidence: 99%